The c-SRC1 gene visualized by in situ hybridization on Xenopus laevis chromosomes - Krylov, V; Mácha, J; Tlapáková, T; Takác, M; Jonák, J (Cytogenetic and genome research, 2003)
Fluorescent in situ hybridization followed by tyramide signal amplification was used to map the site of the c-SRC1 gene on XENOPUS LAEVIS chromosomes. Positive results were obtained with a cDNA probe of about 1 kb. The c-SRC1 gene is located in the subcentromeric region in the long arm of one of the acrocentric chromosomes of the G category (classified according to Graf and Kobel, 1991). The c-SRC1 gene and the XENOPUS major histocompatibility complex (MHC) 1b locus, which consists of 20 tandemly arranged gene copies, are situated on different chromosomes of the G category.
Keywords: geneticky modifikovaná zvířata; Proto-Oncogene Proteins pp60(c-src); Genes, src; mapování chromozomů; protoonkogenní proteiny pp60(c-src); Animals; Animals, Genetically Modified; Xenopus Proteins; hybridizace in situ fluorescenční; Xenopus laevis; zvířata; geny src; Chromosome Mapping; proteiny Xenopus; In Situ Hybridization, Fluorescence